Public investment and budget rules for state vs. local governments - Marco Bassetto (Federal Reserve Bank of Chicago, 2008)
Across different layers of the U.S. government there are surprisingly large differences in institutional provisions that impose fiscal discipline, such as constitutionally mandated deficit or debt limits, or specific tax bases. In this paper we develop a framework that can be used to quantitatively assess their costs and benefits. The model features both endogenous and exogenous mobility across jurisdictions, so we can evaluate whether the different degree of mobility at the local vs. national level can justify different institutional restrictions. In preliminary results, we show that pure land taxes have very beneficial incentive effects, but can only raise limited amounts of revenues. In contrast, under exogenous mobility, income taxes lead unambiguously to insufficient incentives to invest in public capital, unless the fiscal constraints explicitly favor such investment. This conclusion seems to hold even with the introduction of endogenous mobility, since adverse congestion effects from inefficient migration offset the beneficial impact of (partial) capitalization of future taxes into land prices.
Keywords: 330